OPTIC NERVE SHEATH THICKNESS SONOGRAPHY FOR ASSESSING INCREASED INTRACRANIAL PRESSURE: A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2025)
Background: Detecting elevated intracranial pressure (ICP) early and accurately is crucial for this life-threatening condition. A promising non-invasive alternative is the use of optic nerve sheath diameter (ONSD) sonography. This systematic review evaluates the accuracy and reliability of ONSD ultrasonography in identifying elevated ICP, comparing it with traditional methods of ICP assessment. Methods: This systematic review adhered to PRISMA guidelines, utilizing a comprehensive search of PubMed for studies published between 2015 and 2025. The review included cohort studies, cross-sectional studies, randomized controlled trials (RCTs), systematic reviews, and meta-analyses that focused on ONSD sonography for ICP evaluation. Results: ONSD sonography displayed impressive diagnostic accuracy across all 20 studies reviewed, showing a sensitivity ranging from 88% to 100% and specificity between 74% and 98%. The cutoff values for identifying elevated ICP varied between 4.2 mm and 6.7 mm. While inconsistencies in measurement techniques and thresholds persist, many studies have highlighted the effectiveness of ONSD in pediatric populations, intensive care units, and emergency settings. Conclusion: Research indicates that ONSD ultrasonography has both high sensitivity and specificity, establishing it as a valuable and accurate method for detecting excessive intracranial pressure (ICP). As a non-invasive screening tool, it can determine the need for more invasive monitoring while effectively ruling out elevated ICP concerns